Odpowiedzi

2010-02-04T15:53:38+01:00
A)
3(x-½)+2(y+3)=3½
3x-⅓-y+³/₂=-1

3x-1,5+2y+6=3,5
3x-y=-1-³/₂+⅓

3x+2y=3,5+1,5-6
3x-y=-1-⁹/₆-²/₉

3x+2y=-1
3x-y=-1-1¹/₆ |×-1

3x+2y=-1
-3+y=-2¹/₆
-----------------
3y=-3¹/₆ |÷3
y=1¹/₁₈

3x=-1-2×(1¹/₁₈)
3x=³⁸/₁₈ |÷3
x=³⁸/₆
x=6⅓

x=6⅓
y=1¹/₁₈

b)
x-3/4 - y+5/2 = - 1,5
x-3/2 - 2y-7/3 = 1

x-y=-1,5+0,75-2,5
x-2y=1+1,5+2⅓

x-y=-3¼
x-2y=3¹/₆

x=-3¼+y

-3¼+y-2y=3¹/₆

-y=3¹/₆+3¼

y=-6⁵/₁₂

x=-3¼+y
y=-6⁵/₁₂

c)
2x-5/2 - x-6y/4 = x+y/2 |×4
3x-1/10 + 2y-5/5 = 2x+y/2 |×10

4x-10-x+6y=2x+2y
3x-1+4y-10=10x+5y

4x-2x-x-2y=10
3x-10x+4y-5y=1+10

x-2y=10
-7x-y=11

x=10+2y

-7(10+2y)-y=11
-70-14y=11
-14y=81 |÷-14
y=-5¹¹/₁₄

x=10+2(-5¹¹/₁₄)
x=10-11⁴/₇
x=-1⁴/₇

x=-1⁴/₇
y=-5¹¹/₁₄